2017
DOI: 10.1002/ardp.201700090
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carboxamide/Sulfonamide Replacement in Arylpiperazinylalkyl Derivatives on Activity to Serotonin and Dopamine Receptors

Abstract: A series of carboxamide and sulfonamide alkyl (p-xylyl and benzyl) 1-(2-methoxyphenyl)piperazine (o-OMe-PhP) and 1-(2,3-dichlorophenyl)piperazine (2,3-DCPP) analogs were prepared and tested for their affinity to bind to serotonin 5-HT /5-HT /5-HT and dopamine D receptors. This chemical modification let us explore the impact of the replacement of the carboxamide by the sulfonamide group on the affinity changes. In both the o-OMe-PhP and 2,3-DCPP series, the relative activities of the carboxamides versus sulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…For example, the interaction with S5.42, which was considered as a polar and core contact [48,56], caused stabilization of the L-R complex. Contact with N7.39, which was often engaged in ligand binding, being either an acceptor of hydrogen bond [22,24] or forming dipoledipole interaction [48], based on the FMO calculations is a highly attractive interaction. Comparison between serotonin receptorsa case study for ligand 1 For ligand 1, the in vitro activities towards the studied receptors are known ( Fig.…”
Section: Comparison Of Fmo Results With Previous Work For 5-ht 1a Rementioning
confidence: 99%
See 3 more Smart Citations
“…For example, the interaction with S5.42, which was considered as a polar and core contact [48,56], caused stabilization of the L-R complex. Contact with N7.39, which was often engaged in ligand binding, being either an acceptor of hydrogen bond [22,24] or forming dipoledipole interaction [48], based on the FMO calculations is a highly attractive interaction. Comparison between serotonin receptorsa case study for ligand 1 For ligand 1, the in vitro activities towards the studied receptors are known ( Fig.…”
Section: Comparison Of Fmo Results With Previous Work For 5-ht 1a Rementioning
confidence: 99%
“…After all, this contact is observed both in 5-HT 1B and 5-HT 2B crystals [53][54][55] and is mentioned in many modeling studies for various serotonin receptors [11,23,[45][46][47][48][49][50][51]. Considering, for example, the 5-HT 1A receptor (Table 3), docking studies indicated a specific π-π or π-CH hydrophobic interaction [48,56], while optimization of the binding site using the ONIOM method even showed the possibility to form hydrogen bonding to the ligand [22]. This phenomenon, however, can be explained in the context of the adjacent salt bridge with D3.32, which is the anchor point of the ligand, while the repulsive effect may be one of the elements of signal transduction in the receptor, i.e., the interaction causing the change in protein conformation.…”
Section: The Fmo-eda Characteristics Of Studied Serotonin Receptors Bmentioning
confidence: 85%
See 2 more Smart Citations
“…Pharmacophore alignment and scoring engine (PHASE) was used to develop the 3D-QSAR models as a query in searching 3D databases containing "drug-like" small organic molecules and screened against the Asinex Elite synergy database in potency 10 . Unceasing our effort in developing potent 5HT7R antagonists, we have recently done docking studies on the series of compounds [14][15][16][17][18] to obtain a five-point pharmacophore hypothesis AADPR. In order to identify potential hits, the hits obtained were subjected to a rigorous docking process, and drug-like candidates were screened for main interactions with target Human-5HT7 11 .…”
Section: Introductionmentioning
confidence: 99%